Poster No. 023 Indian Consensus for the Utilisation of Combination of Dual Antiplatelet (DAPT) and Statin therapy for the Stratified Treatment of Acute Coronary Syndrome (ACS). (21st October 2022) - Shah, Jay; Kharche, Prashant; Mundhekar, Ajeya; Kumar, Pradeep R; Chaudhuri, Soumik; Sanyal, Joy; Singh, Sukriti Bhalla; Hasan, Omer Mustafa; Kanjilal, Saikat; Mt, Ameya; Azam, Sadiq; Bhupal, V S R; et al.
Abstract: Objective: To formulate a consensus statement for utilisation combination of DAPT and statin combination based on evidence and real-world experiences. Methods: A virtual collaborative educational initiative was convened in June 2022 through a series of nationwide ( n = 16) meetings with 275 cardiologists (cumulative experience of 2, 200-man years) at forefront of ACS management, who rated their level of agreement for 10 questions (6 Likert scale, 4 objective choice). This was preceded by evidence-based discussion of combination of DAPT and statin. Consensus was predefined as > 60% agreeing/disagreeing on any given item. Results: Highest agreement was for the concurrence for clinical relevance of concept of stratified treatment of ACS (95.4%). Agreement score (%) for that DAPT- statin combination is underutilised was 83.8%, followed by the need for optimal management of ACS (75.5%), relevance of BATTLE AMI hypothesis (74.6%), clopidogrel preferred for de-escalated DAPT approach (72.1%), De-escalation therapy is part of optimisation approach (61.8%) ( P < 0.0001). Participants opined that: ischemic risk is the most important factor to choose DAPT (67.6%), other ongoing therapy is an important determinant of DAPT adherence (59.5%), patients with high CV risk are the best suited for prolonged DAPT therapy (46.5%), DAPT should be continued for atleast 1 year (50%). Conclusions: There was a high preference for combination of DAPT and statin for stratified treatment of ACS, associated with a high level of perceived effectiveness based on the recent clinical trials. Combination of DAPT and high potent statin, like rosuvastatin is distinctive in the therapeutic armamentarium for optimal management of ACS.